The endoscopic treatment of fourth ventricle outlet obstruction: Report of two children and systematic review - Ali Mulhem; Abdul Masih Alsulaiman; Stefanie Hammersen; Sven Kantelhardt (Clinical Case Reports, 2023)
Key Clinical Message Fourth ventricle outlet obstruction (FVOO) is a rare cause of hydrocephalus. In the last century, the standard treatment was the suboccipital craniotomy with magendieplasty or ventriculoperitoneal shunt (VP shunt). Since the beginning of the 21st century, the endoscopic third ventriculostomy (ETV) has been considered a less invasive alternative. The medical literature lacks sufficient reports of FVOO cases and strong evidence about ETV's efficacy in treating this condition. We report two cases of FVOO treated with ETV and review published similar cases. Clinical and radiological findings of two FVOO cases with outcomes after ETV were presented. Moreover, we conducted a systematic review after protocol registration in PROSPERO (CRD42021281474). MEDLINE, Embase, Scopus, and Web of Science were searched from inception till December 31, 2022. Studies were included if they reported cases of FVOO treated initially with ETV. Cases with Chiari malformation, Dandy‐Walker malformation, tuberous sclerosis, trapped fourth ventricle, or space‐occupying lesions were excluded. Two reviewers independently examined title/abstract records in the first stage and full‐text publications in the second for eligibility. The primary outcome was the recurrence rate, defined by the need for re‐ETV or other invasive treatments (e.g., VP shunt or magendieplasty). Other outcomes included clinical state at follow‐up and mortality. Two cases, a 3‐year‐old male and 3.5‐year‐old female, with FVOO, were treated with ETV in our department by the same neurosurgeon (SH) in 2013 and 2021. Both cases improved significantly after ETV, and there was no recurrence through the follow‐up. Besides the present cases, we found 57 other cases of FVOO treated with ETV reported in 17 studies between 2001 and 2021. The median age was 26 years, with an IQR from 2.4 to 59 years, and 56% of cases were females. The recurrence rate was 32% in the sample (19 out of 59), with a 95% CI from 21% to 46%. The median time to recure was 2 months with IQR from 1.25 to 26. A VP shunt was the treatment for recurrence in 68% and a re‐ETV in 32%. At the follow‐up (41 ± 29 months), only one case died, and one deteriorated clinically. FVOO is a rare cause of hydrocephalus encountered mainly in the first or sixth decades of life. ETV provides the first reasonable treatment. Despite the moderate recurrence rate, the outcomes are favorable.